Antitoxic, Antifungal and Phytochemical Analysis of Medicinal Compounds of Guiera senegalensis Leaves - Anka, Z.M.; Singh, Vijender; Gimba, S.N.; Singh, Gunjan (Journal of Drug Delivery and Therapeutics, 2020)
Millions of people in the world depend on traditional medicinal plants for treatment of many diseases.  They have curative properties due to presence of various complex chemical substances of different composition, which are found as secondary plant metabolites in one or more parts of these plants. These plant metabolites according to their composition are grouped as flavonoids, tannins, alkaloids, saponins etc. Guiera senegalensis(Gs), which grows in abundance in semi-desert area of Western Africa such as Nigeria, has been used for treating specific diseases and wounds. The study is carried out to investigate the phytochemical analysis, toxicity, and the antifungal activity of Gs leaves extract.Keywords: Guiera senegalensis, Antifungal activity, Brine shrimp, toxicity, phytochemical analysis;